Enhancing Occupational Identity and Self-Efficacy Through a Self-Education Model in Art and Design Education Aligned with Sustainable Development Goals (SDGs) - Xiaodan Yu; Jiraporn Chano; Montree Wongsaphan (ASEAN Journal of Educational Research and Technology, 2026)
This study aimed to enhance students’ occupational identity and self-efficacy in art and design education through a theory-integrated self-education model. Using a mixed-methods approach grounded in Social Cognitive Theory, Vocational Identity Theory, and Career Self-Efficacy Theory, the model was developed and tested with first-year vocational students. The model’s effectiveness was evaluated through pre- and post-intervention assessments and qualitative interviews. Results revealed improvements in identity awareness, career exploration, and self-efficacy dimensions, including problem-solving and career planning. These improvements occurred because the model integrated project-based learning, industry exposure, and structured reflection, enabling students to link learning with future careers. This has implications for achieving Sustainable Development Goals (quality education) by promoting inclusive, relevant, and future-oriented learning frameworks for creative vocational education. The model provides educators and policymakers with a replicable structure for supporting professional growth in rapidly evolving industries.